2004
DOI: 10.1002/elan.200302836
|View full text |Cite
|
Sign up to set email alerts
|

Remote Stripping Analysis of Lead and Copper by a Mercury‐Coated Platinum Microelectrode

Abstract: The performance of a remote stripping sensor based on mercury microelectrodes (MM-RS) for the in situ detection of trace metals in aquatic systems, was investigated. The submersible device employed here consists of a single mercurycoated platinum disk microelectrode assembled in a two-electrode cell configuration, and connected remotely by a 30 m long shielded cable. First, the MM-RS device is characterized in Ru(NH 3 ) 3 6 and Pb 2 synthetic aqueous solutions by applying cyclic voltammetry and anodic strippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Because of the well-known and controllable sphere cap geometry, calibrationless procedures have been proposed to determine lead, cadmium, copper and sulphide ions with mercury-coated platinum disk microlectrodes [43,57,60,89,90]. It has also been shown that this method can be described completely by a set of measurement equations.…”
Section: Mercury Microelectrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the well-known and controllable sphere cap geometry, calibrationless procedures have been proposed to determine lead, cadmium, copper and sulphide ions with mercury-coated platinum disk microlectrodes [43,57,60,89,90]. It has also been shown that this method can be described completely by a set of measurement equations.…”
Section: Mercury Microelectrodesmentioning
confidence: 99%
“…Several recent papers have addressed the above aspects specifically, and in particular have compared SA responses in quiescent and various hydrodynamic or convective conditions (e.g., stirring the solution [60][61][62], vibrating the microelectrode [63], microwave or thermal heating [64,65a-b] of the electrode). It was found that mechanical stirring of the solution was in any case beneficial, but was relatively small at disk and sphere caps (i.e., up to 1.2-1.5-fold enhancements for a hemisphere of 12.5 μm radius and a disk of 15 μm ra- dius, at 300-400 rpm [60,61]), and larger with cylindrical microelectrodes. In addition, it was found that the longer the microwire the greater the effect (i.e, up to 4-fold improvement for a microwire of 2.5 μm radius at 3000 rpm [63]).…”
Section: Mass Transport During the Precon-centration Stepmentioning
confidence: 99%
“…Methods currently available for detecting heavy metal ion analysis include atomic absorption spectrometry [16], X-ray fluorescence spectrometry [17], anodic stripping voltammetry [18], microprobes [19], and inductively coupled plasma mass spectrometry [20]. These element-specific detectors are typically coupled with gas chromatography, high performance liquid chromatography, and capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of SAMs include simplicity of preparation, versatility, stability, reproducibility and possibility to introduce different chemical functionalities [21,22]. As an alternative to environmentally unfriendly mercury- [12] and bismuth- [23] based electrodes several papers related to the detection of metal ions [4,7,24,25] including Cu(II) ions [26][27][28][29] using SAM-modified electrodes have been published recently. However the most of these Cu(II) ion selective electrodes are affected by interfering heavy metal ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical determination of copper has been performed with mercury-coated platinum microelectrodes [12], glassy carbon electrode modified with glyoxime [13], polyphenols [14], phenanthroline [15,16] derivatives and poly-4-nitroaniline [17]. In addition to this, the design of electrodes with controllable surface properties can be achieved using self-assembled monolayers (SAMs), which become popular in the formation of welldefined functional surfaces [18][19][20].…”
Section: Introductionmentioning
confidence: 99%